1998
DOI: 10.1111/j.1540-8175.1998.tb00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Term Results of Dual‐Chamber Pacing in Children with Hypertrophic Obstructive Cardiomyopathy

Abstract: BACKGROUND: Permanent dual-chambered pacing (DDD) is an alternative to surgical treatment in patients with severe hypertrophic obstructive cardiomyopathy (HOCM) who do not have a satisfactory response to medical treatment. METHODS: Five children with severe HOCM still symptomatic despite medical treatment underwent permanent DDD pacing and were followed for 21 +/- 9.7 months. RESULTS: All patients improved their functional class. Doppler echocardiographic studies showed an early reduction of the left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In patients with obstructive hypertrophic cardiomyopathy still symptomatic despite medical treatment, we implanted DDD pacemakers as has already been reported. 31,32 Symptomatic improvement was achieved in all these patients, along with a significant reduction of the gradient across the left ventricular outflow tract. This made it possible to discontinue the medical treatment in all.…”
Section: Discussionmentioning
confidence: 89%
“…In patients with obstructive hypertrophic cardiomyopathy still symptomatic despite medical treatment, we implanted DDD pacemakers as has already been reported. 31,32 Symptomatic improvement was achieved in all these patients, along with a significant reduction of the gradient across the left ventricular outflow tract. This made it possible to discontinue the medical treatment in all.…”
Section: Discussionmentioning
confidence: 89%
“…Small case series in symptomatic children with outflow obstruction noted symptomatic improvement, reduced outflow obstruction, reduced left ventricular hypertrophy, and improved exercise tolerance [34][35][36]. In contrast to early studies [37], later controlled studies found that only about 60% of subjects improved and in the majority of those who benefited, the response was documented to be due to placebo effect and an adverse effect on symptoms was seen in 5% [38].…”
Section: Pacemaker Therapymentioning
confidence: 94%
“…Results in small cohorts of children with outflow obstruction who were symptomatic despite medical therapy noted symptomatic improvement, reduced outflow obstruction, reduced left ventricular hypertrophy, and improved exercise tolerance 3840. Despite early studies 41, subsequent controlled studies found that only about 60% of subjects improved.…”
Section: Familial Hypertrophic Cardiomyopathymentioning
confidence: 99%